Curing characteristics of unsaturated polyester/aramid reinforced composite : microwave vs. thermal energy - Rahmat, A. R.; Day, R. J. (Penerbit UTM Press, 2003)
Conventional curing processes for producing thermoset composites use a thermal approach, which suffers from numerous disadvantages, including a long curing cycle time. This paper reports on an alternative curing process of an unsaturated polyester/aramid composite using microwave energy. The differences in curing characteristic of the composites fabricated between microwave and conventional ovens method were compared. Differential Scanning Calorimeter (DSC) analysis showed that microwave curing of composite was much faster than thermal curing while Fourier Transform Infrared Spectroscopy (FTIR) analysis was found to be very much significant in comparing the conversion of polyester C=C and styrene C=C undergoing microwave and thermal curing.